2016
DOI: 10.1016/j.bbrc.2016.05.144
|View full text |Cite
|
Sign up to set email alerts
|

The regulatory domain of human tryptophan hydroxylase 1 forms a stable dimer

Abstract: The three eukaryotic aromatic amino acid hydroxylases phenylalanine hydroxylase, tyrosine hydroxylase, and tryptophan hydroxylase have essentially identical catalytic domains and discrete regulatory domains. The regulatory domains of phenylalanine hydroxylase form ACT domain dimers when phenylalanine is bound to an allosteric site. In contrast the regulatory domains of tyrosine hydroxylase form a stable ACT dimer that does not bind the amino acid substrate. The regulatory domain of isoform 1 of human tryptopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…In the concentration range of 3-100 μM, NΔ47-TPH2-R eluted as a dimer for all protein loading concentrations and independent of the addition of L-Phe (Figure 2A-B). This is similar to the behavior of the isolated RD of TPH1, which also has been shown to exist as a dimer at protein concentrations above 2.7 μM 27 . Although L-Phe did not affect the oligomeric state of NΔ47-TPH2-R, nanoDSF measurements showed that L-Phe had a stabilizing effect on the dimeric complex with an increase in melting temperature of up to 18 °C, consistent with the presence of a binding site as previously proposed 14 (Figure 2C).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…In the concentration range of 3-100 μM, NΔ47-TPH2-R eluted as a dimer for all protein loading concentrations and independent of the addition of L-Phe (Figure 2A-B). This is similar to the behavior of the isolated RD of TPH1, which also has been shown to exist as a dimer at protein concentrations above 2.7 μM 27 . Although L-Phe did not affect the oligomeric state of NΔ47-TPH2-R, nanoDSF measurements showed that L-Phe had a stabilizing effect on the dimeric complex with an increase in melting temperature of up to 18 °C, consistent with the presence of a binding site as previously proposed 14 (Figure 2C).…”
Section: Resultssupporting
confidence: 81%
“…The N-tail of TPH2 is, similar to TH, longer than that of PAH. It is thus possible that residues in the end of the tail can cover the active site in a state with dimerized RDs, as also discussed by Zhang et al 27 . Although with low confidence, the Alpha-fold 2 predicts residues 1-21 of TPH2 to cover the entrance to the active site (Extended data figure 9) 38 , suggesting at least that this region has a propensity to interact with the CD.…”
Section: Discussionmentioning
confidence: 83%
“…TPH1 is a homo‐tetramer belonging to the family of aromatic amino acid hydroxylases. [90] It is composed of three functional domains: a N‐terminal regulatory domain being able to dimerize, [91] a central conserved catalytic domain, and a C‐terminal oligomerization domain.…”
Section: Structure and Substrate Binding Pockets Of Tryptophan Hydroxylasesmentioning
confidence: 99%